Foliar application of putrescine alleviates terminal drought stress by modulating water status, membrane stability, and yield- related traits in wheat (Triticum aestivum L.) - Wasaya, Allah; Rehman, Iqra; Mohi Ud Din, Atta; Hayder Bin Khalid, Muhammad; Ahmad Yasir, Tauqeer; Mansoor Javaid, Muhammad; El-Hefnawy, Mohamed; Brestic, Marian; Rahman, Md Atikur; El Sabagh, Ayman (Frontiers in Plant Science, 2023)
Terminal stress is the prominent and uprising stress that affects wheat productivity under fluctuating climate scenarios. Foliar application of osmolytes and raising drought-tolerant wheat cultivars can endure drought stress and could be used as a viable option for boosting wheat productivity under terminal drought. The objective of this investigation was to appraise the putrescine foliar application effect on wheat growth and yield under terminal drought stress. Two wheat cultivars i.e. Fakhar-e-Bhakkar and Anaj-2017 were raised under two drought levels i) well-watered (Ww) and terminal drought stress (TDs) at the heading stage. After five days of drought stress imposition, putrescine was foliarly applied. Terminal drought stress at the heading stage decreased the relative water content, membrane stability, specific leaf area, leaf area ratio, spikelet number, spike weight, 100-grain weight, and grain yield. Exogenous application of 1.0 ppm putrescine improved the relative water contents (19.76 %), membrane stability index (78.95%), specific leaf area (41.47%), and leaf area ratio (35.84 %) compared with controlled treatment. Moreover, it also enhanced the spikelet number, spike weight, 100-grain weight, and grain yield with respect to other putrescine treatments. Our findings propose that putrescine foliar application at 1.0 ppm might be used and considered by way of a worthwhile choice for wheat growers to improve grain under arid and semi-arid regions confronted with terminal drought stress.